2011
DOI: 10.1111/j.1468-2397.2010.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary consultation in child protection: a clinical data‐mining evaluation

Abstract: This article presents the results of an evaluation of a multidisciplinary consultation program in child protection by applying a clinical data-mining approach. Using available agency records, data concerning mental health, substance abuse, and domestic violence consultations were extracted retrospectively for evaluative purposes. The results demonstrated that by examining existing records, child-protection practitioners were able to evaluate the existing practices as well as recognize areas for program improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…Child protection workers often lack training in parental mental health (Lalayants et al . ), and drug and alcohol, and a recent study by Hebert et al . () shows that child protection workers can gain significantly from working closely with mental health in terms of their understanding of clients with mental health problems.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Child protection workers often lack training in parental mental health (Lalayants et al . ), and drug and alcohol, and a recent study by Hebert et al . () shows that child protection workers can gain significantly from working closely with mental health in terms of their understanding of clients with mental health problems.…”
Section: Resultsmentioning
confidence: 76%
“…While MH/D&A clinicians and child protection workers both hold significant expertise in their respective domains, neither are ‘experts’ with a full understanding of the complexity of child maltreatment (Lalayants et al . ; Hebert et al . ), perhaps especially so, when it occurs in the context of mental health and drug and alcohol problems.…”
Section: Discussionmentioning
confidence: 99%
“…Another expression of ''fidelity,'' these practice principles favored strength-based, child-centered, family-focused, culturally sensitive interventions. However, in this very different fidelity study, the practitioners were the ''clients'' and consultation patterns revealed significant departures from agency principles as well as variations by consultant expertise (Lalayants, Epstein, & Adamy, 2011).…”
Section: The Cdm Doctoral Dissertationmentioning
confidence: 99%
“…Incluso los problemas que se indican en la categoría de condiciones de trabajo pueden estar detrás de esto, sobre todo los que aluden a la sobrecarga de trabajo que dificult incluso buscar espacios, tanto físicos como temporales, para poder reunirse. En lo que se refiere a los problemas de coordinación externa, los resultados de este trabajo no son una novedad, ya que es un problema ampliamente reconocido (De Paúl, 2009;Jent, et al, 2009;Álvarez et al, 2010;Lalayants, Epstein y Adamy, 2011;World Health Organization, 2014).…”
Section: Discusión Y Conclusionesunclassified
“…También existen dificultade en la coordinación con otros servicios, ya que son conocidos los problemas que se detectan cuando se busca recabar información de otros profesionales, como pueden ser los del ámbito educativo, sanitario, judicial, policial o de salud mental. Esta coordinación resulta compleja en muchas ocasiones (De Paúl, 2009), siendo necesario establecer mecanismos de entendimiento que faciliten una recogida de información eficaz sobre los casos notificados (Jent et al, 2009;Álvarez, Donohue, Carpenter, Romero, Allen y Coss, 2010;Lalayants, Epstein y Adamy, 2011).…”
unclassified